The good have a website: Evidence on website premia for firms from 18 European countries - Joachim Wagner (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2021)
This paper uses firm level data from the World Bank Enterprise surveys conducted in 2019 in 18 European countries to investigate the link between having a website and firm characteristics. We find that firms which are present in the web are larger, older, more productive, and more often exporters, product innovators, process innovators and (partly) foreign owned firms than firms without a website. The estimated website premia are statistically highly significant ceteris paribus after controlling for country and sector of economic activity. Furthermore, the size of these premia can be considered to be large. Good firms tend to have a website.
Keywords: D22; L25; 330; website premia; firm characteristics; World Bank Enterprise Surveys